2018
DOI: 10.1165/rcmb.2016-0428oc
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus θ-Defensin-1 Attenuates Endotoxin-induced Acute Lung Injury by Inhibiting Proinflammatory Cytokines and Neutrophil Recruitment

Abstract: Acute lung injury (ALI) is a clinical syndrome characterized by acute respiratory failure and is associated with substantial morbidity and mortality. Rhesus θ-defensin (RTD)-1 is an antimicrobial peptide with immunomodulatory activity. As airway inflammation and neutrophil recruitment and activation are hallmarks of ALI, we evaluated the therapeutic efficacy of RTD-1 in preclinical models of the disease. We investigated the effect of RTD-1 on neutrophil chemotaxis and macrophage-driven pulmonary inflammation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…As previously highlighted by our group, not only alterations in the systemic, but also in the upper airways immune/inflammatory responses are found after a strenuous and prolonged exercise session, as a marathon race [4]. Elevations of TNF-α and IL-1β—two well-known proinflammatory cytokines—can be verified both in acute and chronic airway inflammation [24,25]. Among some properties, both cytokines are responsible for the neutrophil recruitment in the nasal mucosa, since the combined treatment with anti-IL-1β and TNF-α was able to reduce or even abolish neutrophil infiltration in the nasal mucosa and lung tissue in a model of pathological allergic inflammatory reaction [25].…”
Section: Discussionmentioning
confidence: 91%
“…As previously highlighted by our group, not only alterations in the systemic, but also in the upper airways immune/inflammatory responses are found after a strenuous and prolonged exercise session, as a marathon race [4]. Elevations of TNF-α and IL-1β—two well-known proinflammatory cytokines—can be verified both in acute and chronic airway inflammation [24,25]. Among some properties, both cytokines are responsible for the neutrophil recruitment in the nasal mucosa, since the combined treatment with anti-IL-1β and TNF-α was able to reduce or even abolish neutrophil infiltration in the nasal mucosa and lung tissue in a model of pathological allergic inflammatory reaction [25].…”
Section: Discussionmentioning
confidence: 91%
“…coli sepsis 35 , SARS-coronavirus infection 36 , a mouse model of P . aeruginosa induced cystic fibrosis 37 , and endotoxin-induced lung injury 38 . In a recent study we reported that θ-defensins are potently fungicidal in vitro against MDR C .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the mouse severe acute respiratory syndrome coronavirus model strongly implicated host-directed anti-inflammatory effects of rhesus macaque -defensin (RTD-1) because the pep-tide had no direct antiviral activity (15). RTD-1 was also effective in reducing pulmonary pathology in murine models of endotoxic lung injury (16) and cystic fibrosis (17) by moderating inflammatory responses. Also, RTD-1 arrested joint inflammation in a rat model of rheumatoid arthritis (RA), pristaneinduced arthritis, an autoimmune disease characterized by dysregulated proinflammatory cytokines and erosive joint changes similar to those associated with RA (18).…”
mentioning
confidence: 99%